The drying effect on xanthan gum biopolymer treated sandy soil shear strength. (10th February 2019) - Chen, Chunhui; Wu, Li; Perdjon, Michal; Huang, Xiaoyang; Peng, Yaxiong
Highlights: Xanthan gum has limited effect on the soil strength at initial stage. Drying leads to xanthan gum bonding strength and soil cohesion increase. Shrank brittle dry xanthan gum generates strengthening effect variability in soil. Abstract: Biopolymers are environmentally friendly materials which have shown their competitiveness in civil engineering. Researchers mentioned that drying is the crucial factor in the behaviour of biopolymer treated soil, but how it influences soil strength is still unclear. This study explains how drying influences biopolymer treated soil strength, especially for the behaviour of xanthan gum biopolymer and sand interaction during the drying. The xanthan gum biopolymer presented limited effect in the sand when water content was in a high level. With the continuous evaporation of water, bonding property from the biopolymer gradually showed up which lead to the increase of the soil shear strength (40 °C oven). However, when sample dried at the 20 °C room temperature condition, the outer surface of the sample was cemented and crystallised by the xanthan gum biopolymer while the inner part was still moist and weak cross-linked, which lead to the weak shear strength. When the water became completely evaporated, samples under those two different drying conditions presented a significant increase in shear strength. But these results were inconsistent as the biopolymers shrank and became brittle which lead to a variability of cohesion of soil strength. The measured biopolymer bonding property presented consistent results to the findings in the direct shear tests. The schematic diagram of sand motion was proposed to illustrate the biopolymer treated sand shear performance and gave the further explanation of variability of biopolymer treated sand strength.